Variation in outcomes and practice patterns among patients with localized pancreatic cancer: the impact of the pancreatic cancer multidisciplinary clinic - Pathak, Priya; Hacker-Prietz, Amy; Herman, Joseph M.; Zheng, Lei; He, Jin; Narang, Amol K. (Frontiers in Oncology, 2024)
Patients with localized pancreatic adenocarcinoma (PDAC) benefit from multi-modality therapy. Whether care patterns and oncologic outcomes vary if a patient was seen through a pancreatic multi-disciplinary clinic (PMDC) versus only individual specialty clinics is unclear. Using institutional Pancreatic Cancer Registry, we identified patients with localized PDAC from 2019-2022 who eventually underwent resection. It was our standard practice for borderline resectable (BRPC) patients to undergo ≤4 months of neoadjuvant chemotherapy, ± radiation, followed by exploration, while locally advanced (LAPC) patients were treated with 4-6 months of chemotherapy, followed by radiation and potential exploration. Descriptive and multivariable analyses (MVA) were performed to examine the association between clinic type (PMDC vs individual specialty clinics i.e. surgical oncology, medical oncology, or radiation oncology) and study outcomes. A total of 416 patients met inclusion criteria. Of these, 267 (64.2%) had PMDC visits. PMDC group received radiation therapy more commonly (53.9% versus 27.5%, p=0.001), as compared to individual specialty clinic group. Completion of neoadjuvant treatment (NAT) was far more frequent in patients seen through PMDC compared to patients seen through individual specialty clinics (69.3% vs 48.9%). On MVA, PMDC group was significantly associated with receipt of NAT per institutional standards (adjusted OR 2.23, 95% CI 1.46-7.07, p=0.006). Moreover, the average treatment effect of PMDC on progression-free survival (PFS) was 4.45 (95CI: 0.87-8.03) months. No significant association between overall survival (OS) and clinic type was observed. Provision of care through PMDC was associated with significantly higher odds of completing NAT per institutional standards as compared to individual specialty clinics, which possibly translated into improved PFS. The development of multidisciplinary clinics for management of pancreatic cancer should be incentivized, and any barriers to such development should be addressed.